Quasi-static resource allocation with interference avoidance for fixed wireless systems. - Chawla, K. (IEEE Journal on selected areas in communications)
We propose a novel intercell interference management technique, called quasi-static resource allocation with interference avoidance (QRA-IA), for fixed broadband wireless systems with narrow sectors or equipped with fixed or adaptive array antennas. The basic idea of QRA-IA is for every base to periodically turn off each of its beams (sectors) for a certain amount of time. This periodic turn off introduces a predictable nonuniformity in a terminal's performance and therefore permits each terminal to identify a preferred time period for transmission. QRA-IA requires that each terminal sense the interference over time, select the preferred transmission periods, and report these to the base. The resource allocation algorithm at the base can then use this information for scheduling transmissions to the terminals. The base can also use this information for obtaining an appropriate beam-off sequence. A graph theory model is used to show that an acceptable beam-off sequence exists for each base. A simple, distributed, and measurement-based beam-switching algorithm is designed for the system to find these sequences autonomously. We demonstrate via simulations that a system with QRA-IA provides a marked improvement in the packet error rate performance of terminals over the same system without QRA-IA. This improvement translates directly to improved coverage and throughput and also reduces the burden on higher layer protocols to ensure fairness and quality of service